Optimizing lettuce (Lactuca sativa L.) growth and yield through enhanced light quality in vertical drip fertigation systems - Kumarasena, P. V. D. N. N. T.; Pushpakumari, W. H. Dinesha Udayangani; Chathurika, Jayathunga Arachchige Surani; Rathnathunga, Elpitiya Udari Uvindhya (Talenta Publisher, 2025)
Optimizing light conditions has become crucial for enhancing crop yield, especially in controlled environments like vertical farming. Lettuce (Lactuca sativa L.), highly responsive to light variations, presents an ideal model for studying the influence of light quality on growth. Main objective was to evaluate the effects of light quality on the vegetative growth and yield of two lettuce varieties, ‘Green Coral’ and ‘Red Coral,’ in a home-based vertical drip fertigation system. Completely Randomized Design (CRD) was applied with five replicates and three treatments of T1: Control (no artificial light), T2: two horizontally arranged full spectrum LED light strips, and T3: three horizontally arranged full spectrum LED light strips. Number of leaves (NL), plant height (PH), and fresh weight (FW) were recorded across two growing seasons. Statistical analysis was conducted in one-way ANOVA and Tukey's test revealed that T2 significantly increased NL and PH in both varieties compared to T1 (P<0.05). The variety ‘Green Coral’ showed a significant increase in PH (6.7±0.72 cm) under T2. Wet weight was also significantly higher in T2 for both varieties, with 'Green Coral' yielding 6.2±0.54 g and 'Red Coral' 6.6±0.38 g. These results reported the positive impact of light quality on vegetative growth, suggesting the potential for improved yield in vertical farming.